2014
DOI: 10.1111/trf.12853
|View full text |Cite
|
Sign up to set email alerts
|

Potential risk of blood transfusion‐transmitted brucellosis in an endemic area of China

Abstract: The data indicate a probable high rate of Brucella bacteremia, suggesting a potential risk of transfusion-transmitted brucellosis. Blood donation screening for Brucella infection may be considered in the high Brucella-endemic areas of China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 37 publications
(77 reference statements)
1
16
0
1
Order By: Relevance
“…being affected by brucellosis, it is one of the most widespread zoonosis in the world [1]. Possible routes of acquisition of brucellosis include consumption of derived food products such as unpasteurized milk and cheese, contact with infectious secretions from animals, and rarely human to human transmission through blood transfusion, sexual contact and organ transplantation [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…being affected by brucellosis, it is one of the most widespread zoonosis in the world [1]. Possible routes of acquisition of brucellosis include consumption of derived food products such as unpasteurized milk and cheese, contact with infectious secretions from animals, and rarely human to human transmission through blood transfusion, sexual contact and organ transplantation [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Despite malaria being endemic in some regions of China and previous reports of at least 87 cases transmitted by transfusion from 1992 to 2015 [12], the prevalence of malarial parasites in blood donors is unknown and screening of blood is not [13]. SFTSV, a tick-borne bunyavirus, was first described in China concentrated in the mountainous rural areas in central-eastern China with episodic outbreaks from spring to autumn.…”
Section: Chinamentioning
confidence: 99%
“…Recently, a Brucella spp. investigation based on enzyme immunoassay testing among blood donors in an endemic area (Kashi, Xinjiang province) showed that the reactive rate was 1% (39/3896), in which 0.64% (25/3896) samples were further confirmed by western blot (WB) testing, and the Brucella DNA prevalence rate was 0.39% (15/3896) [105]. Although no infection cases transmitted by transfusion have been reported, the existence of Brucella DNA in donors' plasma samples indicates potential risk of transfusion-transmitted brucellosis in endemic areas and warrants future investigation.…”
Section: Brucellamentioning
confidence: 99%